Profesora Marka Jana Siemka imperium filozofii prawa - Nowak, Ewa (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
In his philosophical opus Marek J. Siemek not only revisited Hegelian two-stage developmental model of the law. He also created his own legal philosophy which is rooted in the tragic conflict of Greek Sittlichkeit. Siemek, however, clearly demonstrates how can an abstract legal system achieve its ethical (sittliche) qualities at modern times, as being mediated by the structures of reciprocal recognition. Siemek’s unique proposal belongs to the neo-positivist and, at the same time, to the post-positivist approaches of the law. The author focuses on the intellectual potential of Siemek’s legal and social thinking as well as on his concept of philosophizing in the era of permanent crisis we experience again today.